Chromium Supplementation for Menstrual Cycle-Related Mood Symptoms. (1st December 2013) - Brownley, Kimberly A.; Girdler, Susan S.; Stout, Anna L.; McLeod, Malcolm N.
ABSTRACT Background: Premenstrual dysphoric disorder (PMDD) afflicts ∼7% of reproductive-age women resulting in impaired relationships, diminished overall quality of life, and disability-adjusted life years lost on par with other major psychiatric disorders. Response to pharmacological treatment is inadequate in ∼50% of women with PMDD. Objective: The goal of the present study is to evaluate the effects of a novel approach—short-term chromium supplementation—on menstrual cycle-related mood and physical symptoms. Methods: Five women were studied under single-blind conditions in a private clinical setting (2 of them were referred specifically for treatment-resistant menstrual-related symptoms); 6 women completed a double-blind crossover study of chromium plus placebo versus chromium plus sertraline in a university clinical research setting. Treatments were administered from mid-cycle to onset of menses in 1-month intervals. Symptom ratings were obtained by self-report, using daily symptom checklists, and by clinical assessment, using the Hamilton Psychiatric Rating Scale for Depression (HAM-D) and the Clinical Global Impressions (CGI) scale. Results: Overall, chromium treatment was associated with reduced mood symptoms and improved overall health satisfaction in most participants. In some cases, chromium alone was associated with marked clinical improvement; in others, chromium plus an antidepressant resulted in greater improvement than either chromium alone or an antidepressant alone. Conclusion: These preliminary observations suggest that chromium may be a useful monotherapy or adjunctive therapy for women suffering from significant menstrual cycle-related symptoms. Larger, controlled studies are needed to evaluate the efficacy of chromium treatment in this patient population.